IDENTIFIKASI UNSAFE ACTION PEKERJA KONSTRUKSI GEDUNG: PERSPEKTIF MANAJEMEN PROYEK PT ‘X’ BUMN JASA KONSTRUKSI - Bagyo, Markus Abu; Iris Mahani; Ima Fatima (Jurnal Teknik Sipil dan Arsitektur, 2026)
The high-rise building construction industry is characterized by a high risk of occupational accidents, where unsafe actions are the dominant cause of incidents. This study aims to identify the most frequent unsafe actions occurring in PT “X” (a state-owned enterprise) building projects to support effective prevention strategies. The research method includes a literature review, validation of indicators by five construction safety experts, development of a Likert-scale questionnaire, data collection from 119 project management respondents via Google Forms, and descriptive analysis combined with a focus group discussion (FGD) to determine intervention priorities. Validity and reliability tests confirmed that the research instrument is appropriate, with Cronbach’s Alpha values ranging from 0.769 to 0.927. Descriptive statistical analysis revealed the three highest-risk behaviors: working while smoking (mean 2.857), storing materials in inappropriate locations (mean 2.832), and improper or incomplete use of personal protective equipment (mean 2.630). Through the FGD, seven unsafe actions were identified as top priorities for intervention, including working in haste, forcing work under unfit physical and mental conditions, and relying on personal work methods that disregard standard procedures. The study concludes that controlling worker behavior through strengthening safety culture, consistent implementation of procedures, effective supervision, and continuous training is essential. These findings are expected to serve as a foundation for developing targeted intervention strategies to reduce accident rates in building construction projects.